Critical Synthesis Package: Clinical Cultural Competency Questionnaire (CCCQ) - Angela P. Wetzel (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Clinical Cultural Competency Questionnaire (CCCQ), and (2) a copy of the pretest version of the CCCQ developed by Bob Like, MD. The CCCQ measures physician knowledge, skills, attitudes, and comfort level associated with the delivery of culturally competent healthcare to diverse patient populations. Eighty-six items are distributed across six domains: Demographics, Knowledge, Skills, Comfort with Encounters/Situations, Attitudes, and Education and Training. These domains are self-assessed by the participant along a 5-point Likert scale using paper and pencil. The measure is available in seven languages. Development of the instrument and initial testing of the instrument with physicians is not documented in the literature. Reliability and validity evidence of modified versions of the CCCQ, applied in pharmacy and medical education and with physicians, nurses, and other hospital staff in practice, indicate high internal consistency and suggest sensitivity of the measure to differences between theoretically meaningful groups. However, the CCCQ lacks evidence of a theoretical framework for the items, and the process of development for the original instrument needs to be explicated. Finally, although not unique to this measure, the CCCQ needs evidence on how scores may predict important patient care outcomes and whether scores remain stable or change over time as anticipated by the theoretical understanding of the construct.